The effect of haemoglobin and blood transfusion on preterm infant gut perfusion and injury - Howarth, Claire; Mifsud, Christian; Banerjee, Jayanta; Eaton, Simon; Leung, Terence; Fleming, Paul; Morris, Joan; Aladangady, Narendra (Frontiers in Pediatrics, 2024)
Introduction: There is significant uncertainty regarding the role that anaemia or red blood cell transfusion (RBCT) plays in the development of gut injury in preterm infants. This study evaluated Near Infrared Spectroscopy (NIRS) together with a range of known biomarkers of gut inflammation to identify their relationship with anaemia and RBCT.Method: A prospective observational study of preterm infants born at <30 weeks gestation was conducted from birth until either 36 weeks post conceptional age or discharge home. Gut perfusion and biomarkers of gut injury were assessed weekly by: 60 minutes NIRS measurements (splanchnic tissue oxygenation index [sTOI] and fractional tissue oxygenation extraction [sFTOE]); stool calprotectin; urine intestinal and liver fatty acid binding proteins (I-FABPs and L-FABPs); and trefoil factor 3 (TFF-3). Exclusion criteria included Fetal Growth Restriction (FGR), and abnormal antenatal Dopplers. Haemoglobin (Hb) levels were measured in parallel with NIRS measurements.NIRS, together with urine and stool biomarkers of gut injury, were evaluated up to 72 hours pre/post RBCT and pre/post measurements compared.Results: Forty-eight infants were studied. Median (range) gestational age was 26 +3 (23 +0 to 29 +6 ) weeks and birthweight 883.5g (460 to 1600). Seven (14.6%) infants developed ≥Bells stage 2 NEC. Infants were in the study for a median of 7.3 (1-13) weeks. There was no significant association between Hb divided into three categories (<80g/l, 80-111.9g/l and ≥120g/l) or continuous values and sTOI, sFTOE or any of the gut injury biomarkers measured (p >0.05). 283 RBCTs were administered; 117 (41.3%) within the first two weeks of life. Pre and post blood transfusion changes in splanchnic NIRS oxygenation, urine and stool gut injury biomarkers were measured in 165, 195 and 175 episodes of RBCT respectively.There was no significant post RBCT changes in splanchnic NIRS or gut injury biomarker levels (p >0.05).Conclusion: There was no association between anaemia or RBCT with NIRS measurements of tissue oxygen saturation and biomarkers of intestinal inflammation or gut injury in preterm infants enrolled in this study. Further studies with standardised methods of examining the relationship between anaemia, RBCT and gut injury are needed.